Strategi Pemasaran Minyak Kelapa Murni (Virgin Coconut Oil) di UD. Cakrawala, Kelurahan Hewuli, Kecamatan Alok Barat, Kabupaten Sikka - Pierina Maya Putri; Yoseph Yakob Da Rato (Jurnal Ilmiah Wahana Pendidikan, 2022)
Pure coconut oil (virgin coconut oil) is a processed product of coconut meat in the form of a clear, tasteless liquid, with a distinctive smell of coconut. At this time has been developed various ways of processing coconut oil such as acidification, addition of oil (fishing), addition of salt (salting), heating, and so on. Pure coconut oil (virgin coconut oil) is also quite in demand by the people of Indonesia, because of its efficacy. Virgin coconut oil is a coconut oil that has a low water content and free fatty acid content, clear color, The purpose of this research is to find out the marketing strategies chosen to develop market share and identify the strengths, weaknesses, opportunities and threats that exist in UD. Cakrawala, Hewuli Village, West Alok Subdistrict, Sikka Regency. A marketing strategy is a unified, broad, integrated, and comprehensive strategy designed to ensure that the goals of the company can be achieved through the proper implementation of marketing by the organization. This research uses SWOT analysis as the basis for determining marketing strategies. Assessment of SWOT analysis based on strengths, weaknesses, opportunities and threats. The results show that the IFE and EFAS matrix, obtained ife score is 2.95 located in the power quadrant and EFE is 2.60 which is located in quadrant I (growth), the strategy applied in this condition is to support aggressive growth policies